2012
DOI: 10.3174/ajnr.a3015
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Leukoaraiosis in Large Vessel Atherosclerotic Disease

Abstract: BACKGROUND AND PURPOSE:The severity of white matter hyperintensity, or leukoaraiosis, is a marker of cerebrovascular disease. In stroke, WMH burden is strongly linked to lacunar infarction; however, impaired cerebral perfusion due to extracranial or intracranial atherosclerosis may also contribute to WMH burden. We sought to determine whether WMH burden is associated with extracranial or intracranial stenosis in patients with AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
4
31
1
Order By: Relevance
“…Our finding of an association of age with WML severity is in line with previous findings [20,29]. In the present study, the previous association of AHT with WMLs [20,29,30] was not replicated, which may be due to heterogeneity of the definition of hypertension including those with diagnosed hypertension under control and those without response.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding of an association of age with WML severity is in line with previous findings [20,29]. In the present study, the previous association of AHT with WMLs [20,29,30] was not replicated, which may be due to heterogeneity of the definition of hypertension including those with diagnosed hypertension under control and those without response.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the previous association of AHT with WMLs [20,29,30] was not replicated, which may be due to heterogeneity of the definition of hypertension including those with diagnosed hypertension under control and those without response. Both the frequency of dyslipidemia and smoking decreased with increasing WML severity, in line with a previous study [20].…”
Section: Discussioncontrasting
confidence: 75%
“…[1] Although LAA commonly coexists with cerebral SVD and shares many risk factors with SVD, [25] these two entities of cerebral vessel disease are thought to had different pathophysiologic mechanisms. [6, 7] Furthermore, the clinical impact of SVD on stroke recurrence in patients with LAA has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies 1012 have suggested that patients with ICAS may be particularly prone to having coexistent SVD, there are limited data on the frequency and risk factors for coexistent SVD and the effect of SVD on stroke recurrence in patients with ICAS who receive medical treatment. The Stenting and Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial 13,14 provided a unique opportunity to investigate these associations.…”
Section: Introductionmentioning
confidence: 99%